Identity, emotion, and feminist collective action - Hercus, Cheryl (Gender and Society, 1999)
This article explores the relationship between identity, emotion, and feminist collective action. Based on interview research, the analysis confirms the central importance of anger in collective action and its particular significance for feminist identity and activism. As an emotion thought deviant for women, the anger inherent in feminist collective action frames created problems for participants in terms of relationships with partners, friends, and work colleagues. Participants performed emotion work to deal with negative responses to their feminist identity, but this depleted emotional energy and created stress. Participation in movement events provided much-needed emotional support and an outlet for deviant emotions.
Keywords: 1900-1999; 1990-1999; australie; colère; discipline; militance; océanie; organisations féministes; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions; étude qualitative

Only the Literal: The Contradictions of Anti-pornography Feminism - Segal, Lynne (Sexualities, 1998)
Within feminism, battles over pornography have become the wars without end. Despite the controversy it generates, the discourses of anti-pornography feminism have continued to make inroads into legal frameworks, most recently in Canada. This piece surveys the growth and questionable appeal of such feminist campaigning, under the theoretical leadership of Catharine MacKinnon: its rewriting of feminist theory; its parasitic relation to the authoritative, phallocentric discourses of gender and sexuality; its alliance with the most reductive, behaviouristic psychology; its disavowel of fantasy and psychic life; its provocative mirroring of both the style and content of the `pornography' it deplores; its unwavering pursuit of legal remedies which enhance the power of state regulation of sexuality; its threat to subversive expressions of women's sexual agency and repudiation of any possibilities for sexual resignifications.
Keywords: cours; discipline; droits des femmes*; histoire et politique; militance; premier cycle; psychologie; ressource en ligne; sciences humaines; sex1911; sexologie; sexualité; thématiques